(untitled) (Third Sector Social Economic Review, 2025)
This study aims to examine the development, trends, and collaboration structures within the scientific literature on magnet hospitals using bibliometric methods. A dataset comprising 544 publications from the Web of Science database, spanning the period from 1988 to 2025, was analyzed using VOSviewer software. The findings are presented under two main categories: performance indicators and science mapping. The performance analysis assessed changes in publication and citation counts over time and identified the most influential authors, journals, institutions, and countries. As part of the science mapping, citation analysis, co-authorship networks (among authors, institutions, and countries), and keyword co-occurrence analyses were conducted. The results reveal a marked increase in research output on magnet hospitals since 2004. Aiken, LH. was identified as the most influential author, the United States produced the highest number of publications, and the University of Pennsylvania emerged as the leading institution in the field. In the keyword analysis, the terms nursing, magnet hospital, and work environment exhibited the strongest link strength. The literature predominantly centers on themes such as improving nurses’ working conditions, strengthening leadership structures, enhancing quality of care, and increasing patient satisfaction. This study contributes to the field by mapping the structural landscape, productivity trends, and collaborative networks of magnet hospital research. It is thought that the study may provide guidance for future research.